Quantifying Landscape Degradation Following Construction of a Highway Using Landscape Metrics in Southern Iran - Mohammadi, Alireza; Fatemizadeh, Faezeh (Frontiers in Ecology and Evolution, 2021)
Rapid expansion of roads is among the strongest drivers of the loss and degradation of natural habitats. The goal of the present study is to quantify landscape fragmentation and degradation before and after the construction of the Isfahan-Shiraz highway in southern Iran. To this end, the ecological impacts of the highway on forests, rangelands, and protected areas were evaluated. Impacts of the construction of the highway were studied within a 1000-m buffer around the road, which was then overlaid on maps of forests, rangelands, and protected areas. Class area, number of patches, largest patch index, edge density, landscape shape index, mean patch size, and patch cohesion index were used to gauge changes in the spatial configuration of the landscape; the ecological impacts of the highway were quantified using effective mesh size, division index, and splitting index. The results indicated that after the construction of the highway, 6406.9 ha of forest habitat, 16647.1 ha of rangeland habitat, and 912 of the Tang-e Bostanak Protected Area will be lost. The effective mesh size metric showed that after the construction of the highway, the area of forest, rangeland habitats and protected area will decrease by 20537, 49149, and 71822 ha, respectively. Our findings revealed drastic habitat loss and landscape fragmentation associated with construction of the highway, serving as references for conservation planning and development.